CHEMISTRY TEACHER'S PERCEPTION TOWARD SCIENTIFIC LITERACY - Zulharveni Zulharveni; Sri Winarni; Erlidawati Erlidawati (FKIP USK, 2022)
Education has a very important role in the development of Indonesian people as a whole. Based on this, it is necessary to develop various sciences in order to improve the quality of learning and intelligence for a nation. Therefore a research has been conducted entitled Perceptions of Chemistry Teachers Against Science Literacy. This study aims to analyze the perceptions of chemistry subject teachers on scientific literacy in several high schools in Aceh. The sample of this research is chemistry subject teachers in Aceh. The approach used in this research is descriptive qualitative. The data collection technique is in the form of an online questionnaire. Based on the results of data analysis and discussion in this study, of the 26 chemistry teachers who filled out a questionnaire, the majority of chemistry teachers had applied scientific literacy to the teaching and learning process after the implementation of the 2013 curriculum. Before the implementation of the 2013 curriculum teachers still often used direct learning. /lecture. Teachers in several areas in Aceh strongly support the application of scientific literacy in chemistry learning. Teachers are eager to take part in the training on scientific literacy that will be held. Professional Learning Community (MGMP) strongly supports the implementation of scientific literacy, especially chemistry lessons.